Understanding, implementing and optimizing SAP processes : tricks, tips and hacks. (Apress, 2022)
This course will help you in your day to day journey with SAP. It covers how to find and use Parameter Id in SAP. Parameter Id personalizes all the daily transaction code and reports you are running and helps you to post and get data based on your requirement. You will learn about the usage of personal value list. This helps SAP users to store their data points inside SAP and use it whenever needed. This course also covers how to create layouts and variants so that you can get different reports and selection based on your daily requirement. This process helps tremendously in reducing error and confusion as you have all the data points pre built. Additionally, you will learn how you can default the values for certain fields in a transaction code so that the number of entries you have to key is much less and it's ready for automation. Finally, you can learn how to default the values in SAP FIORI apps which is the future of user experience and gives the flavor of buying in amazon shopping while running in SAP. This course will help you use SAP in a more productive way with less clicks and optimizing your work. This course will make you the driver that SAP needs it to operate. What you'll learn: how to create default layout and variants How to change your SAP themes and play with different SAP options Learn personal value list which will help you to move all your excel cheat sheet stored in SAP Study parameter Id which will help you to enter less duplicate stuff Who is this book for: Beginning to intermediate end users, SAP S/4HANA users, SAP ECC.